(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Based on the analysis of the performance Lobo, by Carolina Bianchi Y Cara de Cavalo, from 2018, the author hypothesizes that some recent works from the São Paulo scene, produced mostly by women, present convulsive bodies, whose characteristics bring them closer to the descriptions of hysterical bodies of the late 19th and early 20th centuries. She mentions four other works to affirm that there is, in this creative movement, a sign of female empowerment, of affirmation of their “place of screaming.” The author articulates her experience as a spectator with different theoretical and artistic references, incorporating impressions in her writing and recording what she sees in the works. Spectation is used as a methodology, placing this practice between reception and criticism. References external to the performing arts, especially psychoanalysis, contribute to studying the ambivalences and ambiguities put into play.